On the Chemical and Kinematic Signatures of the Resonances of the Galactic Bar as Revealed by the LAMOST-APOGEE Red Clump Stars - Sun, Weixiang; Shen, Han; Jiang, Biwei; Liu, Xiaowei (Astrophysical journal. Letters, 2024)
The Milky Way is widely considered to exhibit features of a rotational bar or quadrupole bar. In either case, the feature of the resonance of the Galactic bar should be present in the properties of the chemistry and kinematics, over a large area of the disk. With a sample of over 170,000 red clump stars from LAMOST-APOGEE data, we attempt to detect the chemical and kinematic signatures of the resonances of the Galactic bar, within 4.0 ≤ R ≤ 15.0 kpc and ∣ Z ∣ ≤ 3.0 kpc. The measurement of the Δ[Fe/H]/Δ∣ Z ∣– R with subtracted global profiles trends shows that the thin and thick disks values are Cor_Δ[Fe/H]/Δ∣ Z ∣ = 0.010 sin (1.598 R + 2.551) and Cor_Δ[Fe/H]/Δ∣ Z ∣ = 0.006 sin (1.258 R − 0.019), respectively. The analysis of the tilt angle of the velocity ellipsoid indicates that the thin and thick disks are accurately described as α = α 0 arctan ( Z / R ), with α 0 = 0.198 sin (0.853 R + 1.982) + 0.630 and α 0 = 0.220 sin (0.884 R + 2.012) + 0.679 for thin and thick disks, respectively. These periodic oscillations in Cor_Δ[Fe/H]/Δ∣ Z ∣ and α 0 with R appear in both thin and thick disks are the most likely chemical and kinematic signatures of the resonance of the Galactic bar. The difference in the phase of the functions of the fitted periodic oscillations for the thin and thick disks may be related to the presence of a second Galactic bar.